2007
DOI: 10.1002/dev.20210
|View full text |Cite
|
Sign up to set email alerts
|

The “smellscape” of mother's breast: Effects of odor masking and selective unmasking on neonatal arousal, oral, and visual responses

Abstract: Lactating women emit odor cues that release activity in newborns. Such cues may be carried in various substrates, including milk or areolar secretions. The present study aimed to examine the responses of infants facing their mother's breast and to sort out the source(s) of active volatile compounds emitted by the lactating breast. Infants (aged 3-4 days) were presented their mother's breast in two consecutive trials of 90 s each: a scentless condition (breast entirely covered with a transparent film) paired wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 37 publications
1
60
0
2
Order By: Relevance
“…In non-human primates, as well as in humans, olfactory and tactile cues serve a key role in the formation of attachment, may function as "hidden regulators" of maternal care (Hofer, 1987(Hofer, , 1995, and initiate a cascade that lead to the supremacy of social gaze reciprocity. For instance, Doucet et al (2007) found that among 3-4 day-old infants odor from breast led to greater infant social gaze and less crying, and 4-month old infants looked longer at faces when exposed to their mother's odor (Durand et al, 2013), suggesting that olfactory cues direct and provide an underlying support to the infant's social gaze behavior. In a decade-long study, we provided full maternal-infant bodily contact in a Kangaroo Care position (a position that integrates touch, odor, proprioception, vision, and audition) to premature neonates who were deprived of full maternal contact and found profound effects of early contact on the development of maternal-infant bonding, gaze synchrony, social outcomes and stress management until ten years of age ).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…In non-human primates, as well as in humans, olfactory and tactile cues serve a key role in the formation of attachment, may function as "hidden regulators" of maternal care (Hofer, 1987(Hofer, , 1995, and initiate a cascade that lead to the supremacy of social gaze reciprocity. For instance, Doucet et al (2007) found that among 3-4 day-old infants odor from breast led to greater infant social gaze and less crying, and 4-month old infants looked longer at faces when exposed to their mother's odor (Durand et al, 2013), suggesting that olfactory cues direct and provide an underlying support to the infant's social gaze behavior. In a decade-long study, we provided full maternal-infant bodily contact in a Kangaroo Care position (a position that integrates touch, odor, proprioception, vision, and audition) to premature neonates who were deprived of full maternal contact and found profound effects of early contact on the development of maternal-infant bonding, gaze synchrony, social outcomes and stress management until ten years of age ).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…This maternal odor appears to guide infants toward the breast and to have a calming effect (Schaal et al, 1980;Doucet et al, 2007). In older children, a preference for maternal odor is present (e.g., Montagner, 1974), and the comforting effect of parental odors is reported by some children (Ferdenzi et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…The latter studies have found that olfaction promotes a range of early regulatory functions. Specifically, odors can modulate infants' arousal states [5]–[6], delay, reduce, or terminate distress and attenuate its physiological correlates [7][8], elicit directional head or body movements [5], [9][11], stimulate breathing and oral-lingual actions [12][14], control ingestive behavior [15]–[16], and initiate the affective tagging of objects/contexts to be approached, avoided, or ignored [17]. In addition, when newborns are exposed to their mother's breast odor, they display longer episodes of eye opening as compared to the same situation with no odor [8].…”
Section: Introductionmentioning
confidence: 99%
“…The result of such exposures is that infants experience temporally and spatially distributed touches, smells, tastes, faces, and voices that give rise to representations of specific people. For example, the nursing-related eye-opening behavior noted in newborns [8] increases over the first weeks [60], so that nursing creates privileged periods during which infants concomitantly perceive, among other stimuli, their mothers' odor and face. Given that odors can rapidly gain affective meaning by association with nurturance [11], [20], specific olfactory experience can be associated with specific visual experience.…”
Section: Introductionmentioning
confidence: 99%